BASICS OF NORMATIVE REGULATION OF CIVIL JUDICIAL PROCEEDINGS IN THE PRINCIPALITY OF SERBIA (1846-1853) - Popović, Miroslav M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The period before the Code of Civil Judicial Proceedings was brought in 1853 is of great importance for researches of Serbian legal history, because legal norms on which civil judicial proceedings in the Principality of Serbia was based were not gathered and analized until now. This paper is a sequel to previous researches and a try to present the way how civil judicial proceedings was regulated before the codification. Тhe bordering years are 1846, when new organizations of courts were brought, and 1853, when the first Code of Civil Judicial Proceedings appeared. In the period 1846-1853 constant work of legislative and executive authorities can be seen with purpose to find solutions for problems which occured in judicial proceedings practise. Civil judicial proceedings was in the first time based on few regulations, they were created as a result of work in progress and judicial practise. Though regulations grew in number and became more precise during time, the lack of code in which all the problems of civil judicial practise would have been covered was felt. The Code of Civil Judicial Proceedings brought in 1853 had many disadvantages, the new one was brought already in 1860. The Code of Civil Judicial Proceedings of 1865 stood on power for almost six and a half decades.
Keywords: Principality of Serbia; civil judicial proceedings; courts; judiciary